Snow accumulation from the Gomez ice core (GZ07), South-western Antarctic Peninsula - Thomas, Elizabeth (Polar Data Centre; British Antarctic Survey, Natural Environment Research Council; Cambridge, CB3 0ET, UK., 2017)
This dataset provides an annual snow accumulation record from the Gomez (GZ07) ice core, dating back to the 1850s. The 136 m core was drilled on the South-western Antarctic Peninsula, during January 2007. The annual accumulation record was derived using two methods: a winter-winter value determined from the winter trough in H2O2 and nonsea-salt (nns) SO4 and a summer-summer value based on the summer peak in H2O2 and nssSO4. Snow accumulation is converted to meters of water equivalent (weq - m) based on measured density profile and correcting for thinning using the Nye model, assuming a linear vertical strain rate through the total depth of the core. The samples were analysed at very high resolution (approximately 10 mm, average 90 samples per year) using the Continuous Flow Analysis with Trace Elements-Dual (CFA-TED) method. The temporal length of the core is 152 years, encompassing 1855-2006 and the estimated uncertainty in the dating is plus/minus 1 year from 1855 to 1875 and less than 1 year from 1875 to 2006.